Assessing the School Management Decision Practices: Insights from the Policy Provisions - Acharya, Bisna; Sigdel, Surya (International Journal of Atharva, 2024)
This study investigates the management decision-making practices of community school management in Nepal, focusing on the policy perspective. An analytical approach has been used to analyze the information. The authors conducted a comprehensive review of the school education policies that pertain to school management decision-making practices. The authors analyzed the policy requirements on community school management decisions and practices. According to the policy provisions, the school head teachers, school management committee (SMC) members, and teachers' representatives are actively engaged in management decision practices. This study reveals that the head teacher and school management committee hold the authority over important aspects of school management decision-making, such as teacher recruitment, school development planning, and teaching learning activities. The role of local government has crucial in the overall development of community schools in Nepal. Implementing effective school management practices can greatly enhance the development of the school and ensure the delivery of high-quality education. In this context, the authors emphasized the importance of harmonizing management practices to ensure effective decision-making and encourage active participation, ultimately leading to improved school administration.